Back Cover: Wearable respiratory sensors for COVID‐19 monitoring (View 5/2022). Issue 5 (29th November 2022) - Chen, Guorui; Shen, Sophia; Tat, Trinny; Zhao, Xun; Zhou, Yihao; Fang, Yunsheng; Chen, Jun
Abstract : The current technological advances in respiratory sensors and their implementations for point‐of‐care monitoring of COVID‐19 are systematically summarized. We highlight the respiratory sensors for biomechanical signal monitoring, such as the respiratory rate and cough frequency, as well as biochemical signal monitoring, such as exhaled breath analysis. Wearable point‐of‐care system enabled by advanced respiratory sensors is expected to promote better control of the pandemic by diagnosis by providing accessible, continuous, widespread, noninvasive, and reliable monitoring of COVID‐19.